2009
DOI: 10.1186/1476-511x-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eicosapentaenoic and docosahexaenoic acid on resting and exercise-induced inflammatory and oxidative stress biomarkers: a randomized, placebo controlled, cross-over study

Abstract: ResearchEffect of eicosapentaenoic and docosahexaenoic acid on resting and exercise-induced inflammatory and oxidative stress biomarkers: a randomized, placebo controlled, cross-over study AbstractBackground: The purpose of the present investigation was to determine the effects of EPA/DHA supplementation on resting and exercise-induced inflammation and oxidative stress in exercisetrained men. Fourteen men supplemented with 2224 mg EPA+2208 mg DHA and a placebo for 6 weeks in a random order, double blind cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 41 publications
5
71
1
5
Order By: Relevance
“…Another hypothesis for the cardioprotective effects of fish oil supplementation is the inhibition of cytokine production, as measured directly in plasma or ex vivo, and studies have been published that support and challenge the hypothesis that n-3 LCP inhibit cytokine and CRP production (102,103,(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150) . In their recent meta-analysis including twenty-one trials, Balk et al (151) concluded that the effect of n-3 LCP, including EPA and DHA, on CRP levels in human subjects was unconvincing.…”
Section: Effects Of Epa and Dha On Inflammationmentioning
confidence: 99%
“…Another hypothesis for the cardioprotective effects of fish oil supplementation is the inhibition of cytokine production, as measured directly in plasma or ex vivo, and studies have been published that support and challenge the hypothesis that n-3 LCP inhibit cytokine and CRP production (102,103,(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150) . In their recent meta-analysis including twenty-one trials, Balk et al (151) concluded that the effect of n-3 LCP, including EPA and DHA, on CRP levels in human subjects was unconvincing.…”
Section: Effects Of Epa and Dha On Inflammationmentioning
confidence: 99%
“…Dietary intake of n-3 fatty acids, and specifically supplementation with docosahexaenoic acid (22:6n-3; DHA), increases blood levels of this fatty acid [11][12][13][14]. A potential increase of unsaturated fatty acids enhances oxidative susceptibility to producing lipid hydroperoxides and oxidative-derived products.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent study, McAnulty et al (2010) noted that supplementation with n-3 fatty acids significantly increased F 2 -isoprostanes after exhaustive exercise. Few studies, however, have determined the effects of such supplementation on the exercise-induced changes in ROS in human subjects (Oostenbrug et al 1997;Bloomer et al 2009). Moreover, in the few studies that have been conducted, the results have been mixed, with the discrepant findings likely due to differences in the exercise protocols, test subjects (trained and untrained), dosage and duration of supplementation, the timing of measurement, and the selection of biomarkers.…”
Section: Introductionmentioning
confidence: 99%